PENGARUH INVESTMENT OPPORTUNITY SET, LIKUIDITAS, DAN KEBIJAKAN HUTANG TERHADAP DIVIDEND POLICY - Andriani, Irma; Putri, Nelly Prima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to empirically prove the influence of investment opportunity set, liquidity and debt policy on dividend policy in companies listed on the Indonesia Stock Exchange in 2020-2022. The type of research used is quantitative with associative methods. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange for 2020-2022. Sampling in this research used a purposive sampling technique with a sample size of 80 companies. The data was processed using the Eviews 9 Statistical Program to test the hypothesis using panel data regression analysis with the REM (Random Effect Model) model which was chosen as the most appropriate model analysis. The research results obtained are (a) There is a significant influence between investment opportunity set and dividend policy. (b) There is a significant influence between liquidity and dividend policy. (c) There is no significant influence between debt policy and dividend policy.Keywords: Investment Opportunity Set, Liquidity, Debt Policy, Dividend Policy